Assessing the Production Potentials of Tomato (Solanum lycopersicum L.) using Two Seed Systems (Formal and Informal) in the Buea Municipality, Cameroon - (:unkn) unknown (My University, 2024)
Tomato (Solanum lycopersicum L.) is the most extensively cultivated fruity vegetable in Cameroon, as its production has the potential to improve food security, as well as income stability for small-scale subsistence farming communities. Most studies on Tomato seed have focused on its response to environmental variations but there exist inadequate information on a comparative study of the use of formal and informal seed systems. This study was thus aimed at assessing the production potentials of two tomato seed systems (T1: Informal seeds, T2: Formal non-hybrid seeds and T3: formal hybrid seeds). Randomized Complete Block Design was used, with three treatments replicated thrice. A sample size of 20 plants were randomly selected from each experimental unit for data collection. T3 had the highest % germination (93%), while T2 had the least (72%). 4WAP, T3 had the tallest plants (69.53 ± 3.07 cm) and T2 had the shortest (50.03 ± 4.31cm), while T1 had the highest girth (8.40±0.75cm) and produced the most leaves (35.93± 6.14). T1 produced the most flowers (73.83 flowers) while T2 and T3 produced 19.83 and 62.93 flowers respectively with T1 producing the most fruits 27.6 as opposed to 4.23 fruits for T3 and 24.43 fruits for T2. T2 had a fruit weight 0.09 ± 0.14 Kg when compared to T1 (6.35 ± 5.67 Kg) and T2 (6.04 ± 4.29) with T1 having the highest fruit diameter (34.97 ± 3.54mm) and highest yield per ha (18.16 ± 16.20 ton/ha). In this studies we conclude that the informal seed system performed better germination percentage, growth and yield component than the formal seed system of tomato.
Keywords: African Research